2010
DOI: 10.1088/0022-3727/43/11/115303
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structures and stability of Ni/Bi2Te3and Co/Bi2Te3interfaces

Abstract: We investigate the electronic structures and stability for Ni/Bi2Te3, NiTe/Bi2Te3, Co/Bi2Te3 and CoTe2/Bi2Te3 interfaces by first-principles calculations. It is found that the surface termination strongly affects the band alignment. Ni and Co are found to form Ohmic contacts to Bi2Te3. The interface formation energy for Co/Bi2Te3 interfaces is much lower than that of Ni/Bi2Te3 interfaces. Furthermore, we found that NiTe on Bi2Te3 is more stable than Ni, while the formation energies for Co and CoTe2 on Bi2Te3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 26 publications
1
29
0
1
Order By: Relevance
“…Besides the Ni, some of other transition metals, such as Co, are also suggested for the metallization layer of n-type Bi 2 Te 2.7 Se 0.3 . [31][32][33] It is reported that Co on Bi 2 (Te, Se) 3 shows significantly less diffusion, even at annealing temperatures at 200 °C. 32 However, the contact made by directly hot pressing Co/Bi 2 Te 2.7 Se 0.3 /Co layered powders at 500 o C has similar contact resistance (~200 μΩ cm 2 ) with that in the case of Ni.…”
Section: Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the Ni, some of other transition metals, such as Co, are also suggested for the metallization layer of n-type Bi 2 Te 2.7 Se 0.3 . [31][32][33] It is reported that Co on Bi 2 (Te, Se) 3 shows significantly less diffusion, even at annealing temperatures at 200 °C. 32 However, the contact made by directly hot pressing Co/Bi 2 Te 2.7 Se 0.3 /Co layered powders at 500 o C has similar contact resistance (~200 μΩ cm 2 ) with that in the case of Ni.…”
Section: Cmentioning
confidence: 99%
“…In addition to the bonding strength, the electrical contact resistance between the electrode and thermoelectric materials needs to be minimized. The contact resistance R c between the electrode and thermoelectric legs decreases the effective <ZT> D of thermoelectric devices according to, 21 , (…”
Section: Introductionmentioning
confidence: 99%
“…It is clearly shown that the specific contact resistivity significantly reduces the leg efficiency and the output power as well. Simply, the specific contact resistivity ρ c between the conducting strip and TE material decreases the effective <ZT> leg of TE devices according to, [34] ( )…”
Section: Introductionmentioning
confidence: 99%
“…В случае контакта к ТЭМ необходимо, чтобы эта величина была не более 10 −8 Ом • м 2 [2][3][4][5][6]. Значительное влияние сопротивления контактов на эффективность термоэлектрических устройств отмечают ряд авторов [2][3][4][5][6][7][8][9]. Автор работы [10] утверждает, что при увеличении контактного сопротивления в термоэлементах, работающих на эффекте Пельтье, до 1% от сопротивления термоэлемента, разность температур (основной его параметр) снижается до 30% от максимального значения.…”
Section: Introductionunclassified